Improving outcome in SubaraChnoid HEMorrhage wIth nAdroparin (ISCHEMIA): a prospective randomised controlled trial protocol - Denneman, Nadine; Doorschodt, Tom C; Coert, Bert A; van den Berg, René; Majoie, Charles B L M; Müller, Marcella C A; Middeldorp, Saskia; Coppens, Michiel; Kempeneers, Marinus A; Tjerkstra, Maud A; Labib, Homeyra; Bandral, Harssh Verdan; et al. (BMJ open, 2025)
IntroductionAneurysmal subarachnoid haemorrhage (aSAH) is a severe condition associated with significant morbidity and case fatality rate. Delayed cerebral ischaemia (DCI) is a major factor contributing to poor outcomes. For long, DCI was thought to be caused by vasospasm, induced by blood in the subarachnoid space. Growing experimental and clinical evidence has shown an activation of the coagulation cascade and several other (intravascular) pathophysiological pathways, affecting the cerebral microcirculation. In a retrospective analysis of our aSAH patient registry, we observed lower in-hospital mortality and a significantly higher rate of discharge-to-home in patients treated with high-dose nadroparin, compared with patients treated with low-dose (prophylactic) nadroparin. This observation suggests a potential benefit of higher doses of nadroparin in the acute course after aSAH. We therefore hypothesise that treatment with high-dose nadroparin will improve clinical outcome in endovascularly treated patients with aSAH.Methods and analysisThis is a single-centre, prospective, phase II randomised controlled trial. From January 2022, all eligible patients will be recruited. 100 patients will be randomised to the intervention arm, that is, nadroparin two times per day 5700 AxaIU, or the control arm, that is, nadroparin once daily 2850 AxaIU in patients with body weight ≤100 kg or once daily 5700 AxaIU in patients with body weight >100 kg, both for up to 21 days. The trial includes a 6-month follow-up period. The primary objective is 30-day mortality rate. Secondary outcomes include assessment of DCI, complications during admission, discharge location, clinical outcome (modified Rankin Scale), quality of life and total healthcare costs at 3 and 6 months follow-up.Ethics and disseminationApproval was obtained from the Medical Research Ethics Committee of the Amsterdam UMC, location Academic Medical Center (AMC) (MREC-number 2020_192), and recruitment has begun. The study results will be submitted for publication in peer-reviewed journals and presented at international conferences.Trial registration numberNCT04507178.